How to respond to climate change at the local level: A guideline for Turkish cities; İklim değişikliğine yerel düzeyde nasıl yanıt verilmelidir? Türkiye Kentleri için Bir Kılavuz - Kerstin Krellenberg; Ethemcan Turhan (Helmholtz-Zentrum für Umweltforschung (UFZ), 2017)
The overall aim of this project was threefold. By organizing workshops at the science-policy interface, the project wanted to: 1. Raise awareness for climate change in Turkish cities and the necessity to develop response action at the local level; 2. Further the exchange between different actors such as academicians, politicians, representatives from the private sector, and civil society as well as between Germany and Turkey in particular; 3. Work on the transfer of solutions to combat climate change at the local level. – – Bu projenin genel hedefi 3 kısımdan oluşmaktadır. Bilim ve politika arabiriminde çalıştaylar organize ederek, 1. Türkiye kentlerinde iklim değişikliği etkileri hakkında farkındalık yaratmak ve yerel düzeyde politika oluşturmak; 2. Devamında akademisyenler, politikacılar, özel sektör tem- silcileri ve sivil toplumdan farklı aktörler ile Almanya ve Türkiye özelinde karşılıklı ziyaretler düz- enlenmesi; 3. İklim değişikliği ile yerelde mücadelede çözümler üzerine çalışmak.
urn:nbn:de:gbv:3:2-80144
Keywords: 330